A survey on Islamic mobile applications for children - Machfud, Fitria Maulida; Mahmud, Murni (IGI Global, 2016)
This paper investigates Islamic mobile applications for children and evaluates the quantity as well as the quality of such applications. The existing and new criteria for exploring Islamic mobile applications used in this study have been enhanced and extended from the level of quality assessment to a deeper aspect of Islamic mobile application's design and interface. Similarly, additional aspects have also been considered to analyse whether it is suitable for children in terms of language, examples used, and whether it is in accordance to the Islamic foundation of Shari'ah that relies on primary and secondary sources of knowledge, which are: Qur'an, Sunnah, and Fiqh Science. The finding shows that there are very few of Islamic apps for children, especially in Malay and Indonesian language. This study suggests that developers should design and develop more Islamic mobile apps for children, especially with education and entertainment features. This study also recommends some requirements and guidelines in designing Islamic apps that are suitable for Muslim children.